Investigating the causal effects of childhood and adulthood adiposity on later life mental health outcome: a Mendelian randomization study - Pathak, Sweta; Richardson, Tom G.; Sanderson, Eleanor; Åsvold, Bjørn Olav; Bhatta, Laxmi; Brumpton, Ben M. (BMC medicine, 2025)
Background Obesity particularly during childhood is considered a global public health crisis and has been linked with later life health consequences including mental health. However, there is lack of causal understanding if childhood body size has a direct effect on mental health or has an indirect effect after accounting for adulthood body size. Methods Two-sample Mendelian randomization (MR) was performed to estimate the total effect and direct effect (accounting for adulthood body size) of childhood body size on anxiety and depression. We used summary statistics from a genome-wide association study (GWAS) of UK Biobank ( n = 453,169) and large-scale consortia of anxiety (Million Veteran Program) and depression (Psychiatric Genomics Consortium) ( n = 175,163 and n = 173,005, respectively). Results Univariable MR did not indicate genetically predicted effects of childhood body size with later life anxiety (beta = − 0.05, 95% CI = − 0.13, 0.02) and depression (OR = 1.06, 95% CI = 0.94, 1.20). However, using multivariable MR, we observed that the higher body size in childhood reduced the risk of later life anxiety (beta = − 0.19, 95% CI = − 0.29, − 0.08) and depression (OR = 0.83, 95% CI = 0.71, 0.97) upon accounting for the effect of adulthood body size. Both univariable and multivariable MR indicated that higher body size in adulthood increased the risk of later life anxiety and depression. Conclusions Higher body size in adulthood may increase the risk of anxiety and depression, independent of childhood higher body size. In contrast, higher childhood body size does not appear to be a risk factor for later life anxiety and depression.